Physical and Morphological Properties of Hard- Soft Ferrite Functionally Graded Materials - Chyad, Fadhi; Jabur, Akram; Abed, Sabreen (Al-Khwarizmi Engineering Journal, 2018)
Functionally graded materials (FGMs), with ceramic –ceramic constituents are fabricated using powder technology techniques. In this work three different sets of FGMs samples were designed in to 3 layers, 5 layers and 7 layers. The ceramic constituents were represented by hard ferrite (Barium ferrite) and soft ferrite (lithium ferrite). All samples sintered at constant temperature at 1100oC for 2 hrs. and characterized by FESEM. Some physical properties were measured for fabricated FGMs include apparent density, bulk density, porosity, shrinkage and hardness. The results indicated that the density increase with the increase the number of layer. Lateral shrinkage is one of the important parameter for estimating the quality of component gradation in an FGM structure. The Vickers hardness show higher value at FGM7, Finally the FESEM images showed a gradation in microstructure within the system from plate- like structure for the hard ferrite to spherical structure for the soft ferrite.